TERRA transcription destabilizes telomere integrity to initiate break-induced replication in human ALT cells - Bruno Silva (Nature Portfolio, 2021)
TERRA RNA has previously been linked to Alternative lengthening of telomeres (ALT). Here the authors developed a tool to rapidly inhibit TERRA transcription from different chromosome ends in an ALT cell line to show that TERRA transcription actively promotes break induced replication (BIR) and destabilizes telomere integrity in ALT cells.